2019
DOI: 10.1017/s0332586519000155
|View full text |Cite
|
Sign up to set email alerts
|

Reunited after 1000 years. The development of definite articles in Icelandic

Abstract: This article traces the diachronic development from the Proto Norse demonstrative hinn via the Old Icelandic definite article(s) to the Modern Icelandic article system. This demonstrative gave rise to two distinct article elements during the Viking period that are well-attested from Old Icelandic onwards, a freestanding and a suffixed article.Based on evidence from Old Icelandic, I argue for a categorial distinction between an adjectival and a nominal article, which does not entirely coincide with a mere morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…(gul-a) hús-ið 'the (yellow) house'. However, for a more detailed account of various patterns in noun phrases with adjectival attributes, see Pfaff (2014Pfaff ( , 2015 concerning present-day Icelandic, and Pfaff (2019) concerning the development from the 13th century onward. 2 I will use the term SUFFIX for the bound post-nominal definite article below, even though this may not be fully correct for Icelandic, as it does not, contrary to e.g.…”
Section: Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…(gul-a) hús-ið 'the (yellow) house'. However, for a more detailed account of various patterns in noun phrases with adjectival attributes, see Pfaff (2014Pfaff ( , 2015 concerning present-day Icelandic, and Pfaff (2019) concerning the development from the 13th century onward. 2 I will use the term SUFFIX for the bound post-nominal definite article below, even though this may not be fully correct for Icelandic, as it does not, contrary to e.g.…”
Section: Notesmentioning
confidence: 99%
“…The article adjective always precedes nouns without the definite suffix 2 ; compare hið ljósa man -*hið ljósa manið. However, these grammatical rules were not settled in Old Icelandic (see Pfaff 2019), whereas an orthographic distinction is manifest as far back as the records go. The neuter form of the demonstrative is normally spelled <tt> or <T> in early manuscripts, in all probability reflecting a long t-phoneme, then as well as now, while the neuter form hið of the article goes back to hit, with a short t-phoneme, normally written <t> in Old Icelandic manuscripts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, it has been suggested that it is the demonstrative itself occurring in postposition that gives rise to the suffixed article, and that is, by and large, the consensus today (e.g. Nygaard 1906, Skrzypek 2009, Stroh-Wollin 20092014;2015a;b;, Perridon and Sleeman 2011, Dahl 2015, Pfaff 2019. We can thus isolate the following parallel developments: While most authors focus on the grammaticalization of the definite article and thus on the development of the suffixed article, I will take a closer look at the adjectival article and its development from a demonstrative, see Sect.…”
Section: From Proto-norse To Old Norsementioning
confidence: 99%
“…D 0 ) in Old Norse (pace Roehrs andSapp 2004, Faarlund 2004;, Lohndal 2007, Laake 2007. Instead, it has long since been suggested that it actually is an element of the adjectival constituent 5 with (h)inn + A forming a unit to the exclusion of the noun (for instance Nygaard 1906, Lundeby 1965, Perridon 1996, Skrzypek 2009, Perridon and Sleeman 2011, Stroh-Wollin 20092015a, Börjars and Payne 2016; Gelenkartikel ("linking article") in Heinrichs 1954, Himmelmann 1997; attributive article in Rießler 2016; adjectival complementizer in Pfaff 2019). In this subsection, 6 I will summarize some arguments in support of the view that it is a narrow component of the adjectival phrase, in that (h)inn together with a weakly inflected adjective constitutes an AP.…”
Section: Adjectival Article "Defective" Adjectives and Adjectival Pmentioning
confidence: 99%